Post-COVID-19 physical and cognitive impairments and associations with quality of life: a cross-sectional study - Rahimi, Fatemeh; Saadat, Maryam; Hessam, Masumeh; Ravanbakhsh, Majid; Monjezi, Saeideh (Frontiers in Sports and Active Living, 2024)
Background and objective This study aimed to compare physical and cognitive functions between post-coronavirus disease 2019 (COVID-19) participants and healthy matched controls and investigate associations between physical and cognitive impairments with quality of life. Methods Twenty-three post-COVID-19 participants and 23 age and sex-matched healthy people without a history of COVID-19 were included. Physical function was assessed using the Medical Research Council Sum Score (MRC-SS), 2 min Step Test, Modified Borg Scale, and Short Physical Performance Battery (SPPB) Test. Cognitive function was assessed using the Montreal Cognitive Assessment (MoCA), Trail Making Test (TMT), and Stroop test, and the quality of life was evaluated using the Euro Quality of Life-5 Dimensions-3 Levels (EQ-5D-3l) questionnaire. Assessments were performed by a physical therapist in one session. Results Mann-Whitney U test showed that in the post-COVID-19 group, compared to the control group, the number of steps in the 2 min Step Test (p < 0.001, ES = 0.57) and the scores of the SPPB (p = 0.03, ES = 0.32), MoCA (p = 0.003, ES = 0.44), Stroop test (p < 0.001, ES = 0.75), and the EQ-5D-3l visual analog scale (p = 0.027, ES = 0.32) were significantly lower. In addition, the Modified Borg Scale score (p < 0.001, ES = 0.6), TMT-A (p = 0.013, ES = 0.36) and TMT-B (p = 0.016, ES = 0.35) times, and the Stroop time (p < 0.001, ES = 0.61) were significantly higher in the post-COVID-19 group. There were no significant between-group differences in the MRC-SS score (p = 0.055, ES = 0.28). Furthermore, there were significant moderate to high associations between physical and cognitive functions and the quality of life in post-COVID-19 participants. Conclusions On average 4 months after symptomatic COVID-19, post-COVID-19 participants had significant impairments in physical and cognitive functions compared to healthy matched controls that were significantly correlated with the quality of life. These findings highlight the need for a comprehensive assessment to plan appropriate management strategies.